Ritual and Religion: The Role of Cultural Practices in Identity Formation - Cahya Munandar, Nilam; Lima, Lucas; Costa, Tiago (Journal of Humanities Research Sustainability, 2024)
Background. This research explores the role of rituals and religion in shaping individual and group identities in various social settings. The background of this research is based on the role of rituals in connecting individuals with their communities and cultural heritage, which gives a deep meaning to collective identity. Purpose. This quantitative study aimed to investigate the preferences of Thai as a foreign language (TFL) learner for ten commonly discussed types of OCF. Specifically, it examined whether these preferences are influenced by four learner variables: proficiency level, first language (L1), foreign language classroom anxiety (FLCA), and foreign language enjoyment (FLE). Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. The findings indicate that, regardless of proficiency level, L1, FLCA, or FLE level, learners prefer more explicit OCF techniques, such as metalinguistics feedback and explicit correction. However, Korean undergraduates scored lower in the majority of OCF strategies (i.e., ignoring, elicitation, recast, explanation, and public feedback) compared to the other participants. Conclusion. This study has significant implications for instructional practices in TFL settings and for L2 lecturers in the classroom. By understanding learners’ preferences for OCF, educators can tailor their instructional approaches to meet the specific needs of their students.